Fluxes and fate of dissolved methane released at the seafloor at the landward limit of the gas hydrate stability zone offshore western Svalbard. Issue 9 (12th September 2015) - Graves, Carolyn A.; Steinle, Lea; Rehder, Gregor; Niemann, Helge; Connelly, Douglas P.; Lowry, David; Fisher, Rebecca E.; Stott, Andrew W.; Sahling, Heiko; James, Rachael H.
Abstract Widespread seepage of methane from seafloor sediments offshore Svalbard close to the landward limit of the gas hydrate stability zone (GHSZ) may, in part, be driven by hydrate destabilization due to bottom water warming. To assess whether this methane reaches the atmosphere where it may contribute to further warming, we have undertaken comprehensive surveys of methane in seawater and air on the upper slope and shelf region. Near the GHSZ limit at ∼400 m water depth, methane concentrations are highest close to the seabed, reaching 825 nM. A simple box model of dissolved methane removal from bottom waters by horizontal and vertical mixing and microbially mediated oxidation indicates that ∼60% of methane released at the seafloor is oxidized at depth before it mixes with overlying surface waters. Deep waters are therefore not a significant source of methane to intermediate and surface waters; rather, relatively high methane concentrations in these waters (up to 50 nM) are attributed to isopycnal turbulent mixing with shelf waters. On the shelf, extensive seafloor seepage at <100 m water depth produces methane concentrations of up to 615 nM. The diffusive flux of methane from sea to air in the vicinity of the landward limit of the GHSZ is ∼4–20 μmol m−2 d−1, which is small relative to other Arctic sources. In support of this, analyses of mole fractions and the carbon isotope signature of atmospheric methane above the seeps do not indicate a significant local contribution from the seafloor source.